MITIGASI UNTUK MENGHADAPI ANCAMAN BENCANA AKIBAT KEGAGALAN TEKNOLOGI NUKLIR DI REAKTOR SERBA GUNA GERRIT AUGUSTINUS SIWABESSY - Dewi Prima Meiliasari; Berton Suar Panjaitan; I Dewa Ketut Kerta Widana (Jurnal Manajemen Bencana (JMB), 2022)
RSG-GAS has a fairly large thermal power of 30 megawatts, besides being useful for health, industry, research, it also has a potential radioactive releases nearby  to the Serpong Nuclear Area about a 5 km radius. The existence of the RSG-GAS in the administrative area of South Tangerang City based on the 2019 Disaster Risk Index has a high risk class for earthquakes and extreme weather, as well as population growth that continues to increase within a radius of 1 km from RSG-GAS, resulting in external hazards from outside the RSG-GAS becoming a threat. in the operation of the RSG-GAS. To be able to reduce potential risk, structural and nonstructural mitigation efforts are needed. This study aims to analyze structural and nonstructural mitigation in the RSG-GAS. The research method used was qualitative with exploratory descriptive research design. The results of the study indicate that structural mitigation has begun to be carried out on the evaluation of site characteristics from the determination of prospective sites to the operation stage for internal and external hazards, the evaluation results are taken into consideration in the design of the RSG-GAS. The RSG-GAS design is capable of both internal and external hazards. Early detection systems can reduce the risk of disaster due to failure of nuclear technology. Nuclear emergency training has been carried out and it is necessary to coordinate the preparation of nuclear preparedness programs at the provincial and national levels. In conclusion, a chain of mitigation efforts has been executed  in RSG-GAS in relation to  the 2020-2024 National Plan on Disaster Management in order to support the national security.